Mutations in EXOSC2 are associated with a novel syndrome characterised by retinitis pigmentosa, progressive hearing loss, premature ageing, short stature, mild intellectual disability and distinctive gestalt. Issue 6 (3rd February 2016) - Di Donato, Nataliya; Neuhann, Teresa; Kahlert, Anne-Karin; Klink, Barbara; Hackmann, Karl; Neuhann, Irmingard; Novotna, Barbora; Schallner, Jens; Krause, Claudia; Glass, Ian A; Parnell, Shawn E; Benet-Pages, Anna; et al.
Abstract : Background: Retinitis pigmentosa in combination with hearing loss can be a feature of different Mendelian disorders. We describe a novel syndrome caused by biallelic mutations in the 'exosome component 2' ( EXOSC2 ) gene. Methods: Clinical ascertainment of three similar affected patients followed by whole exome sequencing. Results: Three individuals from two unrelated German families presented with a novel Mendelian disorder encompassing childhood myopia, early onset retinitis pigmentosa, progressive sensorineural hearing loss, hypothyroidism, short stature, brachydactyly, recognisable facial gestalt, premature ageing and mild intellectual disability. Whole exome sequencing revealed homozygous or compound heterozygous missense variants in the EXOSC2 gene in all three patients. EXOSC2 encodes the 'ribosomal RNA-processing protein 4' (RRP4)—one of the core components of the RNA exosome. The RNA exosome is a multiprotein complex that plays key roles in RNA processing and degradation. Intriguingly, the EXOSC2 -associated phenotype shows only minimal overlap with the previously reported diseases associated with mutations in the RNA exosome core component genes EXOSC3 and EXOSC8 . Conclusion: We report a novel condition that is probably caused by altered RNA exosome function and expands the spectrum of clinical consequences of impaired RNA metabolism.